2020
DOI: 10.3389/fmars.2019.00784
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Mangrove Tree Biomass and Carbon Content: A Comparison of Forest Inventory Techniques and Drone Imagery

Abstract: Measuring Mangrove Biomass With Drones estimates can be made far more quickly and over extensive areas when compared to traditional data collection techniques and, with improved accuracy through further model-calibration, have the potential to be a powerful tool for mangrove biomass and carbon storage estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 33 publications
2
40
1
2
Order By: Relevance
“…Zhang et al (2016) concluded that the normalized differential moisture index (NDMI) provides a sound indicator to assess mangrove forest structure changes. Recent remote sensing approaches have even managed to detect tree species and tree height from space-borne images (Pham et al, 2019;Wang et al, 2019), and to estimate tree biomass from drone images (Jones et al, 2020). Simard et al (2019) used SRTM SAR data, together with spaceborne lidar data, to map the maximum canopy height of mangroves worldwide.…”
Section: Forest Structure and Ecological Processesmentioning
confidence: 99%
“…Zhang et al (2016) concluded that the normalized differential moisture index (NDMI) provides a sound indicator to assess mangrove forest structure changes. Recent remote sensing approaches have even managed to detect tree species and tree height from space-borne images (Pham et al, 2019;Wang et al, 2019), and to estimate tree biomass from drone images (Jones et al, 2020). Simard et al (2019) used SRTM SAR data, together with spaceborne lidar data, to map the maximum canopy height of mangroves worldwide.…”
Section: Forest Structure and Ecological Processesmentioning
confidence: 99%
“…2010 ;Ota et al 2015) juga memberikan hasil yang serupa. Hal ini mengindikasikan bahwa metoda pengukuran dengan menggunakan UAV memberikan hasil estimasi yang cukup akurat dalam perhitungan AGB (Hashem, 2019;Wikantika, 2009;Jones et al 2020;Basuki et al 2009). Untuk memperoleh potensial penyerapan karbon yang maksimum perlu difokuskan pada kegiatan peningkatan biomassa di atas permukaan tanah dibanding karbon dalam tanah disebabkan jumlah bahan organik tanah yang relatif lebih kecil dan masa keberadaannya singkat (Canadell, 2002).…”
Section: Perhitungan Agbunclassified
“…Finally, a percent similarities analysis (SIMPER) was used to determine which tree size and species contributed most to differences found [27,28]. The height of the trees from the ground to the top of the canopy and diameter at breast height (approximately 130 cm from the ground and 30 cm from the highest root in R. mangle) were measured [22,23] and used to classify the trees into four size classes. The size classes were defined as: <40 cm in height (seedlings); from 40 to <150 cm in height (juveniles); >150 cm in height but with <2.5 cm in diameter at breast height (DBH) (young tree); >150 cm in height and DBH between 2.5 to >10 cm (adult trees).…”
Section: Figurementioning
confidence: 99%